2011
DOI: 10.1017/s014338571000091x
|View full text |Cite
|
Sign up to set email alerts
|

Transitivity of Heisenberg group extensions of hyperbolic systems

Abstract: We show that among C r extensions (r > 0) of a uniformly hyperbolic dynamical system with fiber the standard real Heisenberg group H n of dimension 2n + 1, those that avoid an obvious obstruction to topological transitivity are generically topological transitive. Moreover, if one considers extensions with fiber a connected nilpotent Lie group with compact commutator subgroup (for example, H n /Z), among those that avoid the obvious obstruction, topological transitivity is open and dense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…We next consider the case of skew products in higher dimension. In related work, K. Burns and A. Wilkinson studied stable ergodicity of rotation extensions and of more general group extensions over Anosov diffeomorphisms [BW99], and M. Field, I. Melbourne, V. Niţicȃ, and A. Török have analyzed group extensions over Axiom A systems, proving results on transitivity, ergodicity, and rates of mixing [FMT05,FMT07,MNT12].…”
Section: Higher Dimensionsmentioning
confidence: 99%
“…We next consider the case of skew products in higher dimension. In related work, K. Burns and A. Wilkinson studied stable ergodicity of rotation extensions and of more general group extensions over Anosov diffeomorphisms [BW99], and M. Field, I. Melbourne, V. Niţicȃ, and A. Török have analyzed group extensions over Axiom A systems, proving results on transitivity, ergodicity, and rates of mixing [FMT05,FMT07,MNT12].…”
Section: Higher Dimensionsmentioning
confidence: 99%
“…The main result in [48], improving on a weaker result showing only genericity and proven in [49], is:…”
Section: Remarkmentioning
confidence: 99%
“…This approach cannot be applied to nilpotent Lie groups due to the lack of a large set of compact elements. In [11] it is shown that the conjecture holds generically for extensions with fibre the standard real Heisenberg group H n of dimension 2n + 1. Moreover, if one considers extensions with fibre a connected nilpotent Lie group with compact commutator subgroup (for example, H n /Z), among those that avoid the obvious obstruction, topological transitivity is open and dense.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we prove the conjecture for extensions with fibre the standard real Heisenberg group H n . Our approach builds on the techniques developed in [8,10,11,15]. In particular, in [11] results from the classical theory of Diophantine approximation, such as Minkowski Diophantine result for indefinite quadratic forms, come for the first time into play.…”
Section: Introductionmentioning
confidence: 99%